Novel Strategy to Expand Super-Charged NK Cells with Significant Potential to Lyse and Differentiate Cancer Stem Cells: Differences in NK Expansion and Function between Healthy and Cancer Patients - Kaur, Kawaljit; Cook, Jessica; Park, So-Hyun; Topchyan, Paytsar; Kozlowska, Anna; Ohanian, Nick; Fang, Changge; Nishimura, Ichiro; Jewett, Anahid (Frontiers in Immunology, 2017)
Natural killer (NK) cells are known to target cancer stem cells and undifferentiated tumors. In this paper, we provide a novel strategy for expanding large numbers of super-charged NK cells with significant potential to lyse and differentiate cancer stem cells, and demonstrate the differences in the dynamics of NK cell expansion between healthy and cancer patients. Decline in cytotoxicity and lower IFN-γ secretion by osteoclast-expanded NK cells from cancer patients correlates with faster expansion of residual contaminating T cells within purified NK cells, whereas healthy donors’ osteoclasts continue expanding super-charged NK cells while limiting T cell expansion for up to 60 days. Similar to patient NK cells, NK cells from tumor-bearing BLT humanized mice promote faster expansion of residual T cells resulting in decreased numbers and function of NK cells, while NK cells from mice with no tumor continue expanding NK cells and retain their cytotoxicity. In addition, dendritic cells in contrast to osteoclasts are found to promote faster expansion of residual T cells within purified NK cells resulting in the decline in NK cell numbers from healthy individuals. Addition of anti-CD3 mAb inhibits T cell proliferation while enhancing NK cell expansion, however, expanding NK cells have lower cytotoxicity but higher secretion of IFN-. Expansion and functional activation of super-charged NK cells by osteoclasts is dependent on IL-12 and IL-15. Thus, in this report we not only provide a novel strategy to expand super-charged NK cells, but also demonstrate that rapid and sustained expansion of residual T cells within the purified NK cells during expansion with dendritic cells or osteoclasts could be a potential mechanism by which the numbers and function of NK cells decline in cancer patients and in BLT humanized mice.